Historical dredge mining as a significant anthropomorphic agent in river systems: A case study from south-eastern Australia. (July 2021) - Lawrence, Susan; Grove, James; Davies, Peter; Turnbull, Jodi; Rutherfurd, Ian; Macklin, Mark
Bucket dredging to mine and extract gold and tin from rivers is a global industry that has had a range of negative effects on physical environments. These include the destruction of riparian soil profiles and structures, artificial channel straightening and loss of in-stream biodiversity. In this paper we evaluate the immediate effects and long-term consequences of bucket dredging on rivers in Victoria and New South Wales during the period 1900–1950. High quality historical sources on dredge mining are integrated with geospatial datasets, aerial imagery and geomorphological data to analyse the scale of the dredging industry, evidence for disturbance to river channels and floodplains and current land use in dredged areas. The study demonstrates that the environmental impact of dredging was altered but not reduced by anti-pollution regulations intended to control dredging. An assessment of river condition 70–100 years after dredge mining ceased indicates that floodplains and river channels continue to show the effects of dredging, including bank erosion, sediment slugs, compromised habitat and reduced agricultural productivity. These findings have significant implications for river and floodplain management.